A STRUCTURAL EQUATION MODELING ANALYSIS OF WORKLOAD, COMPETEN, AND JOB STRESS ON TRUNOVER INTENTION IN ALFAMART RETAIL STAFF (A Case Study of Alfamart Employees in South Gorontalo City) - Mirnawati Monoarfa; Lisda L Asi; Mohamad Agus Salim Monoarfa (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to determine the effect of workload and competence on turnover intention with work stress as a mediating variable among Alfamart employees in South Gorontalo City. This research employed a quantitative approach with data collection conducted through questionnaires distributed to 62 respondents. Data analysis was carried out using inferential quantitative analysis with SEM-PLS 3.1. The results of the study indicate that: (1) workload has a positive but insignificant effect on turnover intention with an effect value of 7.80%; (2) competence has a positive and significant effect on turnover intention with an effect value of 27.90%; (3) workload has a positive and significant effect on work stress with an effect value of 37.60%; (4) competence has a positive and significant effect on work stress with an effect value of 51.80%; (5) work stress has a positive and significant effect on turnover intention with an effect value of 58.40%; (6) workload through work stress has a positive and significant effect on turnover intention with an effect value of 21.90%; and (7) competence through work stress has a positive and significant effect on turnover intention with an effect value of 30.20%. The R-square value of the turnover intention variable is 60.00%, indicating that turnover intention can be explained by the variables in this study, while the remaining 40.00% is influenced by other variables such as job satisfaction and compensation. The R-square value of work stress is 35.90%, while the remaining 64.10% is influenced by other variables such as the work environment.